Marketing Communication Strategy in Preserving Lok Baintan Floating Market Tourism Destinations, Banjar Regency - Decky C. Kananto LIHU (Indonesia Strategic Sustainability, 2023)
Improvement of the South Kalimantan tourist area to be successful must be made through a partially integrated arrangement and development that remains integrated with other tourist areas, namely the Lok Baintan Floating Market. The researcher analyzes the marketing communication strategy and the process of implementing the marketing communication strategy and tries to find an effective marketing communication model for maintaining and promoting the product image and the existence of the Lok Baintan Floating Market. This research is qualitative, and it can produce descriptive data. Researchers also explore the object under study, with several vital informants who become sources in helping researchers to describe and examine content and marketing communication planning steps carried out through message content design, message design, media and other components as a persuasive communication medium in conveying messages. Tourism products and explain the results of research studies on marketing communication strategy activities. This study uses Austin Babrow's PIT Theory stating that humans have two orientation tendencies: Probabilistic and Evaluative. The researcher made MOKOMPAR LOBA based on the analysis IMC made based on identifying targets, analyzing goals, developing strategies and evaluating processes supporting marketing communication activities programs. MOKOMPAR LOBA describes an integrated marketing communication model, namely the concept of planning the delivery of persuasive communication through integrated marketing communication mix messages.